The Palgrave Handbook of Criminology and the Global South - Carrington, Kerry; Hogg, Russell; Scott, John; Sozzo, Máximo (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
XXIV, 1068 p. 23 illus.